Local and systemic pathophysiological alterations induced by a serine proteinase from the venom of the snake Bothrops jararacussu - Pérez, Aida Verónica (2007)
The local and systemic pathophysiological alterations induced by BjussuSP-I, a thrombin-like serine proteinase from the venom of the snake Bothrops jararacussu, were assessed in mice. BjussuSP-I induced a mild edema but no local myonecrosis or hemorrhage. It did not induce any microvascular alteration in the cremaster muscle. Intramuscular injection of BjussuSP-I promoted an increase in the expression of proMMP-9, but it did not induce the activation of proMMP-2 or proMMP-9 synthesized in muscle tissue injected with a myotoxic phospholipase A2 homolog. BjussuSP-I induced defibrin(ogen)ation upon intravenous and intramuscular injections, with reduction in plasma fibrinogen concentration and increments in the levels of fibrin degradation products and D-dimer. When compared with animals having normal coagulation, mice defibrin(ogen)ated by BjussuSP-I developed a slightly larger hemorrhagic lesion in the skin when injected with metalloproteinase BaP1. Intravenous injection of sublethal doses of BjussuSP-I promoted a series of behavioral and motor changes similar to those previously described for ‘gyroxin’, i.e. opisthotonus and a circular body movement along the longitudinal axis.